Microscopic resection of a giant epidermoid tumor of the pineal region via supracerebellar infra and transtentorial approach with endoscope assistance - Zanini, Marco Antônio [UNESP]; Costa Alves Junior, Aderaldo [UNESP]; Botta, Fabio Pires [UNESP]; Moraes Serpa Nascimento, Haniel [UNESP]; Tadao Hamamoto Filho, Pedro [UNESP] (Journal of Neurosurgery Publishing Group (JNSPG), 2021)
The authors present a case of a 22-year-old male who developed hydrocephalus symptoms related to a giant epidermoid tumor at the pineal region. The surgical approach and technique for a large epidermoid tumor in this area are extensively discussed. A paramedian contralateral supracerebellar infratentorial and transtentorial approach was performed, with the patient in a semisitting position. The tumor was removed using a microscopic technique, and endoscope assistance was used in order to reach the areas unable to be visualized under the microscope. The patient was neurologically intact at his 2-year follow-up, and postoperative MRI showed a significant decrease in the tumoral volume.
Keywords: endoscope assistance; epidermoid tumor; pineal region tumor; supracerebellar infratentorial approach